A Rare Case of Triple-Negative Essential Thrombocythemia in a Young Postsplenectomy Patient: A Diagnostic Challenge. (16th December 2018) - Akcan, T.; Strati, P.; Yan, M.; Idowu, M.
Abstract : The distinction between primary and reactive thrombocytosis by bone marrow histology is very important. Reactive thrombocytosis, the most common cause of thrombocytosis, can be expected in postsplenectomy states; however, close hematological evaluation of prolonged thrombocytosis is essential to identify patients who may have an underlying myeloproliferative neoplasm. We report a 37-year-old woman who was found to have portal, mesenteric, and splenic vein thrombosis with thrombocytosis, two months after she had a splenectomy for spontaneous splenic rupture. Other reactive conditions and myeloproliferative neoplasms (MPN) were excluded, and subsequently, the diagnosis of triple-negative essential thrombocythemia (ET) was established by bone marrow histology. This case of primary thrombocythemia following splenectomy in a young patient illustrates some of the diagnostic difficulties associated with postsplenectomy thrombocytosis. Continuing reports of anecdotal experiences in managing similar complex scenarios is essential and remains the only reference for clinicians facing these rare conditions.